A Multilevel Examination of the Black Middle Class, Segregation, and Neighborhood Crime - Greene, Claire A. (2017)
In The Declining Significance of Race, William Julius Wilson (1987) raised key questions about the fate of urban black class structure and the social organization of black communities in the wake of civil rights era reforms. Unlike in previous decades, Wilson asserted that today’s black neighborhoods comprise almost exclusively of the most disadvantaged segments of the African American population, and therefore lack the basic opportunities, resources, and social controls necessary to reduce crime. In response, this study moves away from a focus on the “ghetto” poor to contextualize the neighborhood crime conditions of middle class blacks. Drawing on social disorganization and structural race theories, I examine the relationship between the black middle class and crime using data from the National Neighborhood Crime Study (NNCS). Results from the multi-level models demonstrate that black middle class family households do effectively reduce neighborhood property and violent crime rates. Subsequent cross-level interaction models suggest that neighborhood property and violent crime decreases as the number of black middle class families in the neighborhood increases, and that this relationship is most pronounced in less segregated cities. Implications and future research directions are discussed